2018
DOI: 10.1111/cga.12309
|View full text |Cite
|
Sign up to set email alerts
|

Ring chromosome 6 in a child with anterior segment dysgenesis and review of its overlap with other FOXC1 deletion phenotypes

Abstract: Here, we report a patient with ring chromosome 6 [r(6)], associated with anterior segment dysgenesis (ASD) and other anomalies. The phenotype was due to a 1880 kb microdeletion at 6p25.3 identified by whole-genome array analysis, and was mainly attributable to a FOXC1 haploinsufficiency. Currently 37 patients with r(6) have been reported. We found that facial dysmorphism, ASD, heart anomalies, brain anomalies, and hearing loss are constant features only in severe cases of r(6), mainly related to hemizygosity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The younger the onset age, the more obvious the clinical phenotype and the more serious the secondary glaucoma. All patients had different levels of posterior embryotoxon and iris hypoplasia which was consistent with previous studies [ 19 ]. Those with severe iris hypoplasia presented obvious pupil abnormalities.…”
Section: Discussionsupporting
confidence: 91%
“…The younger the onset age, the more obvious the clinical phenotype and the more serious the secondary glaucoma. All patients had different levels of posterior embryotoxon and iris hypoplasia which was consistent with previous studies [ 19 ]. Those with severe iris hypoplasia presented obvious pupil abnormalities.…”
Section: Discussionsupporting
confidence: 91%
“…Previous study revealed that FOXC1 was involved in many biological processes, such as eye development [34], cancer [35], cardiovascular system development [36]. Previous studies certified that FOXC1 mutations were associated with the defection of eye anterior segment [37] and cerebral small vessel disease [38]. Human patients with FOXC1 mutations were associated with congenital heart disease [39].…”
Section: Discussionmentioning
confidence: 99%
“…This included 13 individuals with a terminal (n = 10) or subterminal (n = 3) 6p deletion who could be included in our parent cohort. We further included 46 individuals from 28 published papers [ 2 , 4 8 , 21 42 ], 30 with a terminal and 16 with a subterminal deletion, who constitute our literature cohort. We thus included 59 patients in total: 40 with a terminal 6p deletion and 19 with a subterminal 6p25 deletion.…”
Section: Methodsmentioning
confidence: 99%
“…A: Terminal deletion not including FOXC1 (breakpoint distal to 1.61 Mb), B: terminal deletions including FOXC1 and not including TUBB2A (breakpoint between 1.61 and 3.15 Mb), C: terminal deletions including TUBB2A and not including PRPF4B (breakpoint between 3.15 and 4.02 Mb), D: terminal deletions including PRPF4B and not including RREB1 (breakpoint between 4.02 and 7.11 Mb), E: terminal deletions including RREB1 (breakpoint proximal to 7.11 Mb) and S: subterminal 6p deletions (distal breakpoint proximal to 0.35 Mb and including at least part of FOXC1 ). The literature cases were derived from 28 reports [ 2 , 4 8 , 21 42 ]. All deletions are visualised using the UCSC genome browser (GRCh37/hg19) ( https://genome.ucsc.edu ) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%